A descriptive study on the determinants of dental anxiety and coping modes among patients in U.P.C.D. - Galvez, Rica Celina A.
Dental anxiety is fear or apprehension brought about by the dental situation. There are specific causes of dental anxiety, and patients with dental anxiety in turn will do something to cope with the situation. The study was conducted among 63 U.P.C.D. patients to identify specific determinants of dental anxiety and coping modes. An 8-item interview-questionnaire adapted from the Corah Dental Anxiety Scale was used to gather data and content analysis of the subjects' responses were performed. Only 21 (33.33%) of the 63 subjects were found to have dental anxiety. The most common determinants of dental anxiety among U.P.C.D. patients are the fear of pain and the fear of the unknown. The most common coping modes of anxious U.P.C.D. patients are: to think of something else and to breathe deeply. There are various determinants of dental anxiety and coping modes among patients in U.P.C.D. and not all lie within a patient's past or personality, some determinants are within the control of the dentist.